2020
DOI: 10.1111/grow.12435
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of green total factor productivity trend and its determinants for the countries along silk roads

Abstract: In coping with increasing energy consumption and the consequential environmental pollution, green development is becoming an important part of social development. K E Y W O R D S DEA window, green total factor productivity, panel regression, Silk Belt and Road 1712 | PENG Et al. 2 | LITERATURE REVIEW Since Solow (1957) proposed the measure of total factor productivity (TFP) in 1957, research on TFP and its influencing factors has attracted considerable attention. Hu and Wang (2006) proposed the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Macro perspective: The proportion of tertiary industry’s added value to added value of industry is used to measure the industrial structure ( isthi ); the proportion of coal consumption in total energy represents the energy structure ( es ); the proportion of local fiscal expenditure in GDP represents local government control ( admin ) (Ren and Fu, 2019 ; Liu et al, 2020a , b ; Bai et al, 2020 ; Peng et al, 2020 ). Among them, the data of tertiary industry added value, industrial added value, and local fiscal expenditure stems from the China Statistical Yearbook.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macro perspective: The proportion of tertiary industry’s added value to added value of industry is used to measure the industrial structure ( isthi ); the proportion of coal consumption in total energy represents the energy structure ( es ); the proportion of local fiscal expenditure in GDP represents local government control ( admin ) (Ren and Fu, 2019 ; Liu et al, 2020a , b ; Bai et al, 2020 ; Peng et al, 2020 ). Among them, the data of tertiary industry added value, industrial added value, and local fiscal expenditure stems from the China Statistical Yearbook.…”
Section: Methodsmentioning
confidence: 99%
“…Macroperspective: Economic development level ( edl ); population size ( ps ); industrial structure ( issec ); technology import level ( til ); environmental governance intensity ( egi ); and international trade level ( itl ) (Wang et al 2019 ; Zhang et al 2020a ; Peng et al 2020 ). Among these, the permanent population data at the beginning and end of the year are taken from the annual data of the National Bureau of Statistics; GDP, value-added of secondary industry, the amount of energy conservation and environmental protection expenditure, and other data are all from the China Statistical Yearbook in past years; the amount of foreign direct investment in fixed asset investment and total imports and exports are taken from the CSMAR database.…”
Section: Methodsmentioning
confidence: 99%
“…Khan et al (2018) argued that only trade liberalization in middle-income countries can play a role in energy conservation and emission reduction in the long run, while for high-income developed countries, trade liberalization will reduce the total amount of carbon dioxide emissions. Peng et al (2020) asserted that trade openness can optimize the industrial structure to a certain extent, which is beneficial to GTFP. On the other hand, Bandyopadhyay (2006) studied the growth mechanism of GTFP in APEC (Asia Pacific Economic Cooperation) countries and found that trade openness has a negative impact on the growth of GTFP in a country.…”
Section: Studies On the Impact Of Trade Openness On Green Technology Innovationmentioning
confidence: 99%
“…Green BRI construction involves many areas such as green infrastructure [6], green trade [7], green policy, green investment [8], green finance [9], green technology [10], and so on. Meanwhile, relevant scholars have studied the specific measures of green development, such as developing a circular economy [11], improving energy-economic efficiency, adjusting the industrial structure [12], improving green total-factor energy efficiency [13][14][15], improving environmental indicators [16], using renewable resources [17,18], strengthening global environmental governance, and tackling global climate change. Peng et al [13], for example, found that the green total-factor productivity of the countries along the Silk Road economic belt demonstrated increasing trends with time, and factors such as imports, exports, industrial structure, and urban development influenced the growth of green totalfactor productivity.…”
Section: Literature Review 21 Green Bri Constructionmentioning
confidence: 99%